Trend growth and learning about monetary policy rules - Mewael F. Tesfaselassie (Kiel Institute for the World Economy (IfW), 2011)
The paper examines the effect of trend productivity growth on the determinacy and learnability of equilibria under alternative monetary policy rules. It shows that under a policy rule that responds to current period inflation and the output gap a higher trend growth rate relaxes the conditions for determinacy and learnability. Results are mixed for other policy rules. Under the expectations-based rule, trend growth reduces the scope for determinacy but it relaxes the conditions for learnability. Under the lagged-data-based rule rule trend growth reduces the scope for determinacy and learnability.
Keywords: E4; E5; 330; trend growth; learning; monetary policy; determinacy; expectational stability